2019
DOI: 10.1080/02670836.2019.1629541
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and mechanical properties of (AlCoCrFeMn)100 − xCux high-entropy alloys

Abstract: A series of (AlCoCrFeMn)100 −  xCu x high-entropy alloys (0, 4, 8, 12, 16 at.-%) were prepared by vacuum arc furnace melting and their phase composition, microstructure and mechanical properties were systematically investigated. The results show that Cu can induce phase transformation from the orthorhombic phase to the Laves phase in (AlCoCrFeMn)100 −  xCu x high-entropy alloys and the volume fractions of Laves phase increases from 0 to 70% with increasing Cu content. The compression fracture strain increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In contrast, the microstructure of HEAs in some studies (Gwalani et al, 2017) has been relatively fine and uniform, and the ductility and tensile properties of HEAs in these studies have increased with increasing Cu content. Moreover, in other studies (Qin et al, 2019;Yu et al, 2020), the addition of Cu has led to the phase evolution of HEAs, and the mechanical properties of HEAs have been diverse owing to the different phase compositions. Cu has had different modes of effects on HEAs in such studies, so different conclusions have been drawn.…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the microstructure of HEAs in some studies (Gwalani et al, 2017) has been relatively fine and uniform, and the ductility and tensile properties of HEAs in these studies have increased with increasing Cu content. Moreover, in other studies (Qin et al, 2019;Yu et al, 2020), the addition of Cu has led to the phase evolution of HEAs, and the mechanical properties of HEAs have been diverse owing to the different phase compositions. Cu has had different modes of effects on HEAs in such studies, so different conclusions have been drawn.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…For example, a pure Cu phase in interdendritic regions was reported in the Co-Cr-Cu-Fe-Ni system (Verma et al, 2019), and a Cu-rich phase was found in interdendritic regions (Wu et al, 2018). The addition of Cu has also revealed different mechanical properties in different studies (Qin et al, 2019;Yu et al, 2020). Yu et al (2020) posited that uncontrollable Cu-segregation during the casting process leads to ambiguous phase constitution, which induces conflicting conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Cu to AlCoCrFeNi HEA has been shown to enhance the Cu-rich phases in the BCC matrix which results from the positive mixing enthalpy of Cu with other elements that is separated across the matrix region [12,20,21]. Various elements such as Al, Ti, Ni, Cu, and Sn have been tried to improve the HEA matrix hardening through the solid solution and dispersion strengthening mechanisms [22][23][24][25][26]. Joseph et al compared the wear resistance of AlCoCr-FeNi HEA, AISI 304, and Inconel 718 at temperatures > 900 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of elements for HEAs' design is essential when taking the specific applications and economical alloy into consideration [13,14]. A variety of alloys focusing on the influence of different elements on HEAs, such as Al [15], Ni [16], Cu [17], Ti [18], and Sn [19], have been widely published.…”
Section: Introductionmentioning
confidence: 99%